The experimental accreditation mechanism of Mercosur: the construction of a regional quality assurance process for undergraduate courses - Hizume, Gabriella de Camargo; Barreyro, Gladys Beatriz (Universidade Estadual de Campinas, 2017)
This study goals to present and analyze the elaboration and development of the Experimental Mechanism (Mexa) that gave rise to the regional accreditation process of undergraduate courses of the Common Market of the South (Mercosur). For that, the conception of its design, its application, its impacts and its contributions to the establishment of the Regional Accreditation System of Undergraduate Courses were approached. Methodologically, the research was based on documentary analysis and interviews with people who participated in the elaboration and / or application of the Mechanism, focusing on the actions of the Member States that founded the bloc. It was verified that if on the one hand it is possible to consider that the Mexa favored the culture of the evaluation and the accreditation of the higher education in the region, bringing as achievement the joint construction of the whole process by its participants, on the other, the limitations of its experimental character created some problems for the regional process, hindering its application on a large scale.